THE APPLICATION OF QRQC METHOD TO SOLVE PROBLEMS AND TO IMPROVE THE PRODUCTION FLUX (2) - Ancuta BALTEANU; Jan GRIGORE; Mihaela ISTRATE; Monica BÂLDEA (Fiabilitate şi Durabilitate)
The subject proposed was developed over two parts. In the first written work it was presented the initial situation within a production flow that is sensed in the appearance of defects and nonconformities in obtain the final products. In this second paper - respectively this - we will show the use of this method in a situation that requires elimination of a technological problem appeared in the production flux and in relieving its positive consequence.